Manajemen Pendidikan Karakter Siswa Berbasis Boarding School - Neng Fitri Aulia; Nova Nurhakim (Islamuna: Jurnal Studi Keislaman, 2025)
Character education is a crucial and integral part of the Indonesian education system. It plays a vital role in shaping students’ behavior and moral values. This study aims to examine the management process of the boarding school at SMA Gemayasih Cibungur, particularly in developing students’ character through daily activities. This research employed a qualitative descriptive method. The study was conducted at SMA Gemayasih, involving the dormitory head, school principal, dormitory supervisors, and staff as research subjects. Data were collected through observation, interviews, and documentation.The findings indicate: (1) the planning of character education at SMA Gemayasih is based on the boarding school model and aligned with the school’s vision, mission, and goals; it emphasizes character value habituation and refers to national character values; (2) the implementation and supervision involve teachers guiding students through practices such as Duha prayer before lessons and applying the 5S principles (Smile, Greet, Salute, Politeness, Courtesy); (3) evaluation is carried out through regular monthly and annual meetings involving both teachers and students to review the effectiveness of character education programs.